Performance enhancement of α-MnO2 through tunnel-size and morphology adjustment as pseudocapacitive electrode. (1st May 2023) - Ji, Xu; Luo, Haowei; Dong, Wenju; Yang, Lexuan; Guo, Jianjun; Cheng, Shuang
Abstract: As a typical pseudo-capacitive electrode material, α-MnO2 always suffers from low practical capacity and poor stability because of the low conductivity and unavoidable disproportionation reaction. In the work here, high valance Mo (Mo 6+ ) doping followed by chemical reduction treatment is proposed to mitigate these issues. It is found that morphology of the α-MnO2 can be influenced by Mo-doping, and tunnel size is tuned by the following reduction. Without doping, α-MnO2 nanorods with good crystallization can be obtained. With the increase of Mo feed ratio, the length of the nanorods is gradually reduced and fine nanoparticles are formed when the Mo/Mn feed mole ratio reaches 1:20 (named as R-1:20). With this feed ratio, a largely increased capacity of 245 C g −1 at 0.5 A g −1 is achieved, much larger than that of the pure α-MnO2 nanorods (110 C g −1 ). Yet, there is a certain distortion of the crystal structure, resulting in decline of rate performance. Meanwhile, cycling performance also decays owing to the increase of active sites and hence disproportionation reaction. After reduction treatment, tunnel size of the R-1:20 are slightly enlarged, leading to the improvement of rate performance and cycling stability, and 93% of the initial capacity is maintained after 10, 000 cycles. Mo-doping and the following reduction treatment can effectively increase the activity sites, increase the electronic and ionic conductivity, suppress the disproportionation reaction through the adjustment to morphology and tunnel size, and thus improve the charge storage capability of α-MnO2 .